Problem-Based Learning Method Using Comic As A Medium Toward Studentsâ€™ Learning Outcomes Of Economy Social Science in Uang dan Lembaga Keuangan - Taryadi, Taryadi; Rusdarti, Rusdarti (Universitas Negeri Semarang, 2018)
Uang dan Lembaga Keuangan are materials of Economy Social Science subject which mostly use lecture and memorization in its learning process. This leads to studentsâ€™ inability to develop their potential and makes students passive. Therefore, a learning method which can trigger studentsâ€™ activeness is needed. One of the learning methods that can improve the quality of learning is Problem-Based Learning Method and the use of comic as a medium in learning.The objective of this study is to determine whether there are different activities and learning outcomes between the students who learn using a Problem-Based method and comic as the learning medium and the students who learn using a conventional method in class IX SMP Nasima Semarang.This research used Quasi-Experimental Design design with Nonequivalent Control Group Design form. The population in the study was 108 students of class IX of SMP Nasima Semarang with two sample classes, which were class IX-A and IX-C with 28 students in each class.Initial data of the research used the result of pretest which showed the average score of the experimental class was 70,95 while the average score of control class was 70,83. Based on the statistically processed data by using â€œtâ€ test, the t-count was 2.441, while the value of t-table was 2,004. Therefore, it could be concluded that t count > ttable, then with this Ha was accepted while Ho was rejected. It showed that there were differences in students' learning outcomes between the experimental group and the control group after they were given different learning methods. The class which learned through problem-based learning method had better outcomes than the class which learned through a conventional method.